2012
DOI: 10.1158/0008-5472.can-11-1403
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Genes Upregulated in ALK-Positive and EGFR/KRAS/ALK-Negative Lung Adenocarcinomas

Abstract: Activation of the EGFR, KRAS, and ALK oncogenes defines 3 different pathways of molecular pathogenesis in lung adenocarcinoma. However, many tumors lack activation of any pathway (triple-negative lung adenocarcinomas) posing a challenge for prognosis and treatment. Here, we report an extensive genome-wide expression profiling of 226 primary human stage I-II lung adenocarcinomas that elucidates molecular characteristics of tumors that harbor ALK mutations or that lack EGFR, KRAS, and ALK mutations, that is, tri… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

25
657
1
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 732 publications
(685 citation statements)
references
References 37 publications
25
657
1
2
Order By: Relevance
“…Previous reports have demonstrated that DEPDC1 is up-regulated in bladder cancer (Kanehira et al, 2007), breast cancer (Kretschmer et al, 2011) and lung cancer (Okayama et al, 2012). To our knowledge, our report is the first one showed DEPDC1 up-regulation in HCC.…”
Section: Discussionsupporting
confidence: 58%
See 2 more Smart Citations
“…Previous reports have demonstrated that DEPDC1 is up-regulated in bladder cancer (Kanehira et al, 2007), breast cancer (Kretschmer et al, 2011) and lung cancer (Okayama et al, 2012). To our knowledge, our report is the first one showed DEPDC1 up-regulation in HCC.…”
Section: Discussionsupporting
confidence: 58%
“…Given that DEPDC1 is also up-regulated in bladder cancer (Kanehira et al, 2007), breast cancer (Kretschmer et al, 2011) and lung cancer (Okayama et al, 2012), it is crucial to unveil how DEPDC1 is regulated in future study. Researchers found DEPDC1 was up-regulated in bladder cancer tissues, but undetectable in 24 normal human tissues except in testis (Kanehira et al, 2007), and developed peptide vaccine based on this cancer/testis antigen, which effectively induced peptide-specific cytotoxic T lymphocyte in vivo (Obara et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We queried Gene Expression Omnibus (GEO) with the keyword “lung” and with the platform set to “GPL570” or “GPL96,” and then selected datasets with a sample size of more than 30. As a result, we got six datasets on platform GPL570, including GSE10245 (n = 40), 34 GSE19188 (n = 110), 35 GSE30219 (n = 83), 36 GSE31210 (n = 224), 37,38 GSE37745 (n = 91), 39 and GSE50081 (n = 128), 40 and five datasets on platform GPL96, including GSE10072 (n = 107), 41 GSE14814 (n = 71), 42 GSE31547 (n = 50), 43 GSE68465 (n = 353), 44 and GSE7670 (n = 54). 45 Detailed information about the datasets is presented in Table 1; the sample numbers are the result of removing patients treated with chemotherapy or radiotherapy.…”
Section: Methodsmentioning
confidence: 99%
“…21 We used the criteria of false discovery rate o0.1 and log 2 fold change 41.5 or o − 1.5. To evaluate the relationship between LAMC2 mRNA expression level and prognosis in NSCLC, we used three publicly available mRNA microarray data: the first cohort of 204 ADCs from Japanese National Cancer Center (JNCC set; HG-U133A Plus 2.0; GSE31210), 46 the second cohort of a mix of 63 ADCs and 75 SCCs from the Samsung Medical Center (SMC set; HG-U133A Plus 2.0; GSE8894), 47 and the third cohort of 59 ADCs and 52 SCCs from Duke University Medical Center (DUMC set; HG-U133A Plus 2.0; GSE3141). 48 Detailed methods were described in the Supplementary section.…”
Section: Methodsmentioning
confidence: 99%